THE IMPACT OF HUMAN CAPITAL ON THE EFFICIENCY OF SCIENTIFIC RESEARCH AND INNOVATION IN THE MODERN ECONOMY - GORODETSKA, Tetiana; LARINA, Tetiana; LYPOVYI, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article aims to examine the impact of human capital on the effectiveness of scientific research and innovation in the modern economy by establishing interconnections that contribute to the growth of innovation potential and the enhancement of economic system competitiveness. The article considers human capital as a key factor in ensuring the competitiveness of contemporary economies, as it enhances the efficiency of scientific research, fosters innovation development, and supports sustainable economic growth. In a globalized world and under technological progress conditions, human capital investment becomes essential for maintaining economic development. It has been determined that in modern conditions, human capital includes both traditional components, such as knowledge and qualifications, and social aspects, including creativity, loyalty, responsibility, and entrepreneurial thinking. Therefore, human capital development directly affects economic growth by increasing labor productivity, commercializing scientific knowledge, and implementing innovations. Investment in education, scientific research, professional training, and public health contributes to income growth, improved living standards, and expanded consumer opportunities, as highly qualified specialists generate new knowledge and technologies, strengthening the competitiveness of national economies. It has been proven that science and education are critical components of human capital development. They form society’s intellectual resources through cooperation between scientific institutions, businesses, and government bodies, which creates conditions for the commercialization of scientific developments and the accelerated implementation of innovations. Furthermore, advancing digital competencies and information technologies significantly expands human capital opportunities, facilitating adaptation to global challenges and ensuring economic stability. It has been established that human capital serves as the foundation of economic development, playing a key role in innovation-driven transformation processes and strengthening countries’ positions in the global market. Investments in human capital, particularly in science, technology, and education, are strategically crucial for shaping a sustainable future and fostering economic prosperity.